Diversificación agrícola, su importancia en el manejo de plagas en cultivo de arroz (Oryza sativa L.) para una agricultura sostenible - Marquínes Ortega, David Anthony (2022)
Crop diversification includes the planting of several single crops, i.e., belonging to exclusive families, on the same farm's land. It aims to avoid soil depletion and provide better use of fertilizers, in addition to promoting pest management (weeds, insects and others). Farmers who practice monoculture in rice production find that it is more difficult to manage pests in their fields. Pests are more intensive and damaging on tillage sites that have only one type of crop on an annual basis. In fact, it is not always unexpected, because pests have their habitat and host in the same place for a long time, so they reproduce more easily. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose of informing the reader about agricultural diversification, its importance in the management of pests in rice (Oryza sativa L.) for sustainable agriculture. From the above, it was determined that, in rice production, crop rotation and integrated pest management can greatly help to avoid some of the fundamental terrible effects of monoculture. Annual crop rotation interrupts pest cycles and keeps the soil in a more balanced state in terms of its composition. Diversification in rice cultivation allows the control of major pests such as Legworm (Tibraca limbativentris), Locust (Spodoptera frugiperda), Stem Borer (Diatraea saccharalis), Earworm (Oebalus ornatus), Torch Virus and Pyricularia